Calf Management practices followed by dairy farmers in Kopargoan Taluka of Ahmednagar district of Maharashtra - Lata Sharma; Jayant Khadse; Ashok Pande (Journal of Livestock Biodiversity, 2025)
A study was conducted to understand and get an idea about the calf management practices followed by dairy farmers in Kopargoan taluka of Ahmednagar district in Maharashtra. A survey format was designed to collect the data by using telephonic interview method of the farmers through BAIF farmers call center “Sanvadini”. A total of 713 farmers from 15 villages were selected for survey, out of which 309 randomly selected farmers were interviewed by using formal questionnaire. Criterion of farmer’s selection was farmers having an average herd size of 3–4 milking cows. Data on deworming, vaccination, dehorning and colostrum feeding was recorded. To assess consistency in management, farmer’s perception was recorded to indicate whether they followed scientific approaches for effective calf management. Results indicate that 65.70, 67.64 and 70.55 percent farmers were practicing dehorning, vaccination and deworming respectively. Total 87.06 percent farmers were feeding the colostrum to the calves with an average 2.9 days. There is inconsistency in calf management practices as colostrum feeding is very common in the studied areas. As in modern milk production system, calves are often overlooked, it was also found that veterinary advices or services are seldom used for calves; treatments are performed primarily by calf raisers especially by women. This requires attention of extension workers, veterinary field practitioner to create awareness among farmers about importance of these practices. Increased knowledge about calf rearing is important to maintain good health of calf and to milk production.